GAMBARAN KEMANDIRIAN GIZI MASYARAKAT DAN PELAYANAN KESEHATAN SERTA KEJADIAN KEP DI DESA SIAGA KOTA PROBOLINGGO - Leersia Yusi Ratnawati (Universitas Jember, 2015)
Desa Siaga was a village that has self-supporting skill to prevent and overcome health problems. This program has purpose to increase community knowledge and awareness about health, to increase community ability and desire in health self supporting. It was a descriptive research to describe the nutritional self -supporting, public health service and Protein Energy Malnutrition(PEM) Prevalence (using Weight for Age Index, WHO/NCHS standard) in some Desa Siaga in Probolinggo City. Sampling tehcnique was using Purposive Sampling. The result showed that community nutritional self-supporting was good. It was showed by good nutritional knowledge and practice, good emergency reaction on nutritional problem, and nutritional garden ownership by respondent. But, it was need an increasing of public health service in every community area and the using of the service also. Those potencial aspects can be a modal to decrease PEM prevalence and develop Desa Siaga Program. Keywords: Community Nutritional Self-Supporting, Public Health Service, Protein Energy Malnutrition